Potential of ento-tourism in Segaliud Lokan forest reserve, Sabah - Franey Joseph Chong; Fiffy Hanisdah Saikim; A.Y.C. Chung; R. Japir; A.D Dg Fazrinah (Sabah Forestry Department, 2024)
Entomological tourism, a specialized ecotourism sector, is becoming acknowledged for its ability to offer distinctive and educational experiences focused on insects. This type of tourism takes advantage of the allure and variety of insects, appealing to enthusiasts, researchers, and nature lovers. The increasing interest in sustainable and educational travel has created a chance to investigate and admire the complex ecosystems influenced by insects through entomological tourism. This abstract explores the fundamental elements of entomological tourism, such as its educational significance, conservation ramifications, and economic advantages. These activities are gaining popularity and help foster public appreciation of insects, but their forms and techniques differ. Studying the timing of insect sightings during recreational and tourism activities can offer valuable information on how to enhance insect conservation through ecotourism, a component typically neglected in biodiversity conservation plans. This multidisciplinary study is new and has limited scope in both entomology and tourism sciences. When conducted with appropriate and ethical standards, entomological tourism can enhance the link between humans and the world of insects, leading to increased environmental awareness and local community development. This paper delves into the different aspects of entomological tourism, emphasizing its importance as a possible driver for biodiversity conservation, scientific research, and the advancement of sustainable tourist practices, and the SWOT analysis were conducted for this field to see the relevance.